Modelling the acceptance factors to use enterprise technology (Intranet) in a successful telecommunication industries in Malaysia / Farah Dayana Mohammad Asri - Mohammad Asri, Farah Dayana (Faculty of Business and Management, 2015)
Enterprise technology can enhance the productivity of workers. Many organizations have implemented many types of IT system for their employees but have not yet studied the acceptance of the technology by their employee populations. This study is aimed to determine the acceptance factor of Enterprise Technology (Intranet) users in successful telecommunication industries. This is done by few supported theory such as, Technology Acceptance Model (TAM) and extended theory of TAM is Theory of Reasoned Action (TRA). The selected factors in the framework are Perceived Usefulness (PU), Perceived Ease of Use (PEOU) and Perceived Performance (PF). Survey questionnaire was used to collect the data needed, which was adapted and modified from the previous researchers. The respondents were employee from one of the successful telecommunication industries in Malaysia. Data collected was analyzed using SPSS and the methods of analysis were frequency analysis, reliability analysis, descriptive statistics and Pearson’s correlation. The findings of this study revealed that there were significant correlation between PU( r=0.736 P=0.000), PEOU( r=0.723, p=0.000), PF( r=0.759, p=0.000) and AUET.